RAHASIA SEJARAH TERSEMBUNYI: EKSPLORASI ISLAM, BUDAYA, DAN SOSOK WALIYULLAH BANYUWANGI - Maulida, Isna; Silvi, Silvi Nur Dina; Putri Andiyani, Siti Aisyah; Rahma Febrian, Valentino; Hafsoh, Asiatul; Prasetya Ersa, Dita Ragil; Majidatul Maghfiroh, Mirna; Rahmatullah Amrozi, Shoni (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2024)
This study identifies, analyzes, and evaluates the role of Mbah Datuk Malik Ibrahim and Mbah Mas Moch Shaleh in spreading Islam in Banyuwangi. Which includes the method of spreading Islam, what challenges were faced in spreading Islam, the origin and environment in Banyuwangi, the development of Hinduism and Buddhism, and the arts in the Blambangan museum. The research method we use is a qualitative method in which we make observations by going directly to the field and interviewing the relevant sources. The results showed that the city of Banyuwangi, which was once a majority, adhered to Hinduism and Buddhism, which can be seen from the existence of the Blambangan kingdom, until that time the spreaders of Islam came to the city of Banyuwangi, namely Mbah Datuk Malik Ibrahim and Mbah Mas Moch Shaleh, whose grave evidence is still there today, which is precisely in the Lateng Banyuwangi area. The entry of Islam in Banyuwangi did not escape the struggle of the two figures above. Both figures spread Islam in their own way, such as Mbah Datuk who spread Islam because of his expertise in religious knowledge through preaching. While Mbah Mas Moch Shaleh spread Islam because of his expertise in spiritual science, namely in terms of medicine.